Lessons learned from building the kid’s trial with an online children’s and parents’ research advisory group: a descriptive, qualitative study - Simone Lepage; Barbara Whelan; Laura Flight; Nikki Totton; Declan Devane (Research Involvement and Engagement)
Abstract Health research increasingly incorporates public and patient involvement (PPI) to enhance trial inclusivity and relevance, and it is often mandated by funding and regulatory bodies. PPI boosts public engagement with trials and aligns trial objectives more closely with the priorities of the groups they aim to benefit. The Kid’s Trial, an online randomised trial co-created with children, aims to help them better understand what randomised trials are, why they matter, and improve their critical thinking skills. To ensure inclusivity and relevance, we established two PPI groups: the Children’s Research Advisory Group (CRAG) and the Parents’ Research Advisory Group (PRAG). We recruited a representative sample of children and parents from diverse ethnic, geographic, and socioeconomic backgrounds to reflect the trial’s target demographic. We engaged PPI group members through social media and email campaigns aimed at parents of children aged 7 to 12. PPI meetings were conducted online, followed set agendas, and included real-time trial updates, post-meeting feedback surveys, and polls. A PPI compensation plan was established in advance. Online interviews later captured their insights and experiences as PPI partners. Seven family units, comprised of eight children and seven parents, were recruited over 15 weeks from six countries. PPI partners shaped the trial design by contributing to website animations, aesthetic changes, and language adaptations. Interviews were analysed using reflexive thematic analysis to explore the facilitators, challenges, and outcomes of participating in our online research advisory groups. Reflections from researchers and PPI partners demonstrated that participation in the advisory groups enhanced children’s learning and confidence. Many members, including children and adults, experienced unexpected positive outcomes, such as increased scientific literacy, science communication and confidence. Their involvement meaningfully shaped the trial’s development and processes. This study also provides guidance for researchers engaging similar demographics in future PPI activities.